Mutant of adeno-associated virus capsid protein, nucleic acid for coding mutant and application of mutant - PAN OUDONG; YANG JIALI; SHEN WEIRAN; YANG XINGLIN; CAI ZEQI; NIU LELE (2024)
The invention discloses a mutant of adeno-associated virus capsid protein, nucleic acid for encoding the mutant and application of the mutant. The mutant of the capsid protein of the adeno-associated virus has amino acid mutation at one or more of the 1301 < th > site, the 1708 < th > site and the 1711 < th > site relative to the capsid protein of a parent AAV9. Virus particles prepared by using the mutant of adeno-associated virus capsid protein give consideration to both transduction efficiency and targeting, and can provide a safer and more effective gene therapy vector tool for subjects. 本申请公开了一种腺相关病毒衣壳蛋白的突变体、编码其的核酸及应用。该腺相关病毒衣壳蛋白的突变体相对于亲本AAV9的衣壳蛋白在第1301位、第1708位和第1711位中的一位或多位具有氨基酸突变。使用该腺相关病毒衣壳蛋白的突变体制备得到的病毒颗粒，兼顾了转导效率和靶向性，能够为受试者提供更安全、更有效的基因治疗载体工具。